5r+7=3r-5

Simple and best practice solution for 5r+7=3r-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5r+7=3r-5 equation:



5r+7=3r-5
We move all terms to the left:
5r+7-(3r-5)=0
We get rid of parentheses
5r-3r+5+7=0
We add all the numbers together, and all the variables
2r+12=0
We move all terms containing r to the left, all other terms to the right
2r=-12
r=-12/2
r=-6

See similar equations:

| 6=x10+ | | 5*2-x)=-10 | | 12-y=14 | | 17y-14(17y+4)=5027 | | -7(6+d)=-70 | | 3x-5=2x-4+ | | 3x+6+1=8 | | 18=6+2d | | -0.4=g-4.5 | | 3x-5=2x-40 | | 5m÷3=4÷9 | | -3g=2 | | m3+ 9= 13 | | b/17-7b/17=48/17 | | 11/12x=560 | | 11/12x=569 | | X+.07x=4.78 | | 5x-20=10x-15 | | 7x+5x+x=180 | | 2=7+r8 | | |20-7x|=8 | | 3x-2(3x-12)=60 | | (x+1)(x-1)(x-4)(x+4)(x-5)=0 | | 4(2k-8)=k+1 | | 1+8k=-5+7k | | 8x+15x=115 | | -25=-312+x | | 3c-38=4c-55 | | Y+1=(3x-4) | | m+1013=2 | | 6x–2+3x=–2x+6–5x | | 25=(-8)+9(x+3) |

Equations solver categories